Survey of marketing research in Singapore - Chin, Wey Chwan (2014)
Marketing research which was introduced to Singapore only in the 60s is a relatively new field in the Singapore business scene. The group’s primary purpose in initiating a report on this subject is to gain a better understanding of the local corporate perception of marketing research as well as its likely role in the future.